A compensation model developed to liberalize spectrum in the G4 era - Yuntsai Chou (International Telecommunications Society (ITS), 2014)
Because fourth-generation(4G) mobile communications services are rooted in heterogeneous multibands, a unified managementregime fails toaccommodate spectral heterogeneity. This study examined an adequate regimein the 4G era that maximizes spectrum efficiency. A conjoint analysis was conducted to assert the policy preferences of Taiwan's mobileoperators, including second generation(2G), third generation(3G), andwireless broadband access(WBA) operators. The results of the conjoint analysis indicated that the WBA operators were highly supportive of spectrum usage rights,such as technologyand service neutrality and secondary trading. The 3G-only operators prioritize no granted tender period after license expiration, whereas the 2G incumbents mostly emphasize refarming on their bands. Regulatorsareencouraged tocreate a differentiated spectrum management regime that tailor individual firms' needs and increase their willingnessto efficiently use spectra. First, the WBA operatorsshould be allowed for secondary trading in their underusedspectrum. Second, the 2G and 3G operatorsshould be able to perform refarming. Finally, the recall of the 2G bands should be mandated once the 2G incumbents fail to satisfy the set efficiency criteria to avoid hoarding behaviors. Thus, the differentiated spectrum management regime could neutralize the propagation characteristics of different bands to maximize long-term use efficiency.
Keywords: 330; spectrum management; spectrum usage rights; tender period; technology neutrality; serviceneutrality; secondary trading; recall; refarming; spectrum caps